Application of PEG400 in the one-pot synthesis of 7-[4-alkyl- or (hetero)aryl-1H-1,2,3-triazol-1-yl]thieno[3,2-b]pyridines via SNAr and Cu(I)-Catalyzed Azide-Alkyne Cycloaddition and preliminary evaluation of their anti-tumour activity - Rodrigues, Juliana M. (2018)
Several novel 7-[4-alkyl- or (hetero)aryl-1H-1,2,3-triazol-1-yl]thieno[3,2-b]pyridines were prepared in good to high yields, using the environmentally friendly solvent PEG400 in a one-pot procedure from 7-chlorothieno[3,2-b]pyridine to form the corresponding azide via SNAr with NaN3, followed by Cu(I)-catalyzed Azide-Alkyne Cycloaddition (CuAAC) using different types of alkynes. This one-pot reaction in PEG400 starting from a halogenated heteroaromatic system is reported for the first time and demonstrated a wide scope of application for alkynes. Preliminary anti-tumour activity on human tumour cell lines using the prepared 1,4-di(hetero)aryl-1,2,3-triazoles was evaluated, together with their toxicity in non-tumour cells. Among the tested compounds the most promising one was a 2-ethynylpyridine derivative.